Abiotic stress responses in plants: roles of calmodulin-regulated proteins - Virdi, Amardeep S.; Singh, Supreet; Singh, Prabhjeet (Frontiers in Plant Science, 2015)
Intracellular changes in Ca2+, one of the important secondary messenger molecules, in response to different biotic and abiotic stimuli are detected by various sensor proteins in the plant cell. Calmodulin (CaM), one of the most extensively studied Ca2+-sensing proteins, is involved in the transduction of signals. Following interaction with Ca2+, the Ca2+-bound CaM (Ca2+-CaM) undergoes conformational change and regulates the activities of a diverse range of proteins. Several of the CaM-binding proteins are also implicated in stress response of plants, indicating that CaM plays an important role in enabling the plants to adapt to adverse environmental conditions. Stress adaptation in plants is a highly complex and multigenic response. Therefore, identification and characterization of proteins that are modulated by CaM under different abiotic stress conditions is imperative for unraveling the molecular mechanisms responsible for abiotic stress tolerance in plants. Functional characterization has revealed involvement of CaM in the regulation of metal ions uptake, generation of reactive oxygen species and modulation of transcription factors such as CAMTA3, GTL1 and WRKY39. Activities of several kinases and phosphatases are also modulated by CaM, thus providing further versatility to plants in signal transduction and stress responses. The results obtained in contemporary studies are consistent with the proposal that CaM acts as an integrator of several different stress signaling pathways that allow plants to maintain homeostasis through negative and positive regulation of different cellular processes. The present review summarizes the progress made so far in understanding the role of CaM in modulating different stress-regulated proteins and their implications in enhancing the tolerance of plants to abiotic stresses.